The genus Pinnularia (Bacillariophyta) excluding the section Distantes on Livingston Island (South Shetland Islands) with the description of twelve new taxa - Zidarova, Ralitsa; Kopalová, Kateřina; van De Vijver, Bart (Phytotaxa, 2012)
During the ongoing revision of the non-marine diatom flora of Livingston Island (South Shetland Islands, Maritime Antarctic Region) the taxonomy and morphology of all Pinnularia taxa, excluding the section Distantes, present in the samples from Livingston Island, have been analysed. Seventeen different Pinnularia taxa have been recorded. Apart from those previously described from the Antarctic Region (P. subcapitata var. elongata, P. gemella, P. austroshetlandica) and the Andes (P. strictissima), thirteen unknown taxa have been found. Based on their unique morphological features, twelve are described as new in this paper: P. australodivergens sp. nov., P. australoglobiceps sp. nov., P. australomicrostauron sp. nov., P. australoschoenfelderi sp. nov., P. hamiltonii sp. nov., P. livingstonensis sp. nov., P. magnifica sp. nov., P. microstauroides sp. nov.,  P. pseudolaucensis sp. nov., P. sergiplaiana sp. nov., P. subcarteri sp. nov. and P. subaltiplanensis sp. nov. For one, only a few specimens have been found and at present they cannot be identified with 100% certainty.